Upaya Peningkatan Kemampuan Geometri Siswa SMP ST. Antonius Padua Sentani Melalui Pendekatan Matematika Realistik - Yacob Ruru; Ida M. Hutabarat; Radian J. Situmeang; Halle F.P. Watori (LPPM Uncen, 2026)
Conceptual understanding is central to geometry learning, yet many junior high school students find geometric objects and their properties highly abstract. This community service program was conducted at SMP St. Antonius Padua Sentani, Jayapura Regency to strengthen Grade VIII students’ understanding of plane and solid geometry through a Realistic Mathematics Education (RME) approach. The program used context-based problems, concrete manipulatives, guided discussions, and structured practice. Program effectiveness was evaluated using a one-group pretest-posttest design (n=20). The mean score increased from 34 (pretest) to 41 (posttest) with an N-gain of 0.11 (low). Although the learning gains were modest, the activities improved student engagement and supported the transition from contextual situations to formal geometric representations. The results suggest that continued implementation and repeated cycles of RME-based instruction with richer tasks and longer duration are needed to achieve stronger learning gains.